Dual acting nuclear receptor targeting conjugates : design, synthesis and biochemical evaluation - Kelly, Patrick M. (Trinity College (Dublin, Ireland). School of Pharmacy & Pharmaceutical Sciences, 2013)
Breast cancer has become the second most common cancer worldwide after lung cancer, the fifth most common cause of cancer death, and the foremost cause of cancer death in women. Worldwide, breast cancer exceeds all other cancers and the incidence rates of breast cancer are increasing steadily. The vast majority of early stage breast cancers, in both pre- and postmenopausal women, are hormone-dependent. The human hormone estradiol (E2) plays an important role in the progression and development of the tumour. One of the major therapeutic advances in clinical treatment of breast cancer has been the introduction of selective estrogen receptor modulators (SERMs). The key feature of the SERMs, which are chemically diverse compounds, is that they contain a tertiary structure that enables them to bind to the estrogen receptor. Another important chemotherapy class are vascular targeting agents such as antimitotic drugs which target the microtubules and their dynamics. They interact with various tubulin binding sites and disrupt the role that microtubuies play in the tumour cell cycle. Microtubuies play a major part in mitosis and cell division, and for this reason they are an important target for anticancer drugs.
Keywords: Pharmaceutical Chemistry, Ph.D.; Ph.D. Trinity College Dublin